Essential content of evidence‐based clinical practice guidelines for bladder cancer: The Japanese Urological Association 2015 update. (3rd July 2016) - Kubota, Yoshinobu; Nakaigawa, Noboru
Abstract: The Japanese Urological Association revised the clinical practice guidelines for bladder cancer in April 2015. This was the first update carried out in the 6 years since the development of the initial clinical practice guidelines for bladder cancer in 2009. The descriptive content was revised, and additions were made with a focus on new‐found evidence and advances in the latest medical practices, and on the basis of the increasingly aging population observed in the underlying social context in Japan. An algorithm for the treatment of bladder cancer has been presented as a new trial. In the present article, we will introduce the essential contents and clinical questions that address the present revisions.